An experimental study on the operational characteristics of a direct expansion based enhanced dehumidification air conditioning system. (1st September 2018) - Chen, Wenjing; Chan, Ming-yin; Weng, Wenbing; Yan, Huaxia; Deng, Shiming
Highlights: A novel enhanced dehumidification air conditioning (EDAC) system was proposed. There were two evaporators in the EDAC system for improving humidity control. The operational characteristics of the EDAC system were experimentally studied. The EDAC system was proved to provide variable output latent cooling capacity. Abstract: Once a conventional On-Off controlled single evaporator direct expansion air conditioning (A/C) system is installed, it has to be operated at different seasonal cooling load situations, and hence would have a hard time in trying to maintain the desired indoor thermal environment at all times, unless complicated and costly supplementary measures to provide variable dehumidification capacity are provided. Therefore, a novel standalone enhanced dehumidification air conditioning (EDAC) system was proposed based on multi-evaporator air conditioning technology. There were two evaporators in the proposed EDAC system, and the mass flow rates of both refrigerant and air to both evaporators can be varied. This paper reports on an experimental study on the operational characteristics of a prototype experimental EDAC system with both evaporators operated. Using the prototype experimental EDAC system, extensive experimental work has been carried out. During the experiments, constant compressor and supply fan speeds were used, but the refrigerant and air mass flow rates to both evaporators were varied, at different inlet air states to the experimental EDAC system. The experimental results demonstrated that at a fixed inlet air state, varying refrigerant and air mass flow rates to both evaporators led to outputting varied total cooling capacity (TCC) and equipment sensible heat ratio (E SHR) from the experimental EDAC system. For example, at an inlet air state of 26 °C and 50% RH, TCC varied from 4.5 kW to 5.32 kW and E SHR from 0.63 to 0.7. Furthermore, TCC and E SHR were mutually constrained within an irregular area in a TCC - E SHR diagram. Different inlet air states would result in shifted position of, or varied shape of an irregular area. Therefore, the use of the proposed EDAC system could provide variable output sensible and latent cooling capacity to deal with variable indoor space thermal load, so that achieving better indoor humidity and thus thermal control is possible with the proposed EDAC system.